Japan : 2008 Article IV Consultation; Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that Japan's external position remains strong. The current account surplus rose to 4.8 percent of GDP in 2007 on the back of strong external demand and a further surge in investment income. Money markets remain relatively stable owing to the banking system's lower exposure to subprime and other securitized products and the increased amounts and frequency of the Bank of Japan's (BoJ) liquidity operations. The near-term economic outlook is for a soft landing, although there remain risks from the global economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet